2005
DOI: 10.1063/1.2044487
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and scaling for convection of isolated structures in nonuniformly magnetized plasmas

Abstract: Large-scale radial advection of isolated structures in nonuniformly magnetized plasmas is investigated. The underlying mechanism considered is due to the nonlinear evolution of interchange motions, without any presumption of plasma sheaths. Theoretical arguments supported by numerical simulations reveal an inertial scaling for the radial velocity of isolated structures in the ideal limit. This velocity increases as the square root of the structure size relative to the length scale of the magnetic field. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
163
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(177 citation statements)
references
References 29 publications
9
163
1
Order By: Relevance
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35] During their radial propagation, the blob-like structures develop a steep front and a trailing wake, which can also be observed in numerical simulations of isolated blob structures [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] and simulations of scrape-off layer turbulence. [51][52][53][54][55][56][57][58][59][60][61] Conditional averaging of experimental measurement data have shown that large-amplitude fluctuations are well described by an exponential wave form.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35] During their radial propagation, the blob-like structures develop a steep front and a trailing wake, which can also be observed in numerical simulations of isolated blob structures [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] and simulations of scrape-off layer turbulence. [51][52][53][54][55][56][57][58][59][60][61] Conditional averaging of experimental measurement data have shown that large-amplitude fluctuations are well described by an exponential wave form.…”
Section: Introductionmentioning
confidence: 99%
“…(8). The stability of small blobs (d < 1) is determined mainly by the Kelvin-Helmholtz (KH) instability, 37,121 whereas the stability of larger blobs (d > 1) is determined primarily by curvature-driven instabilities. 37,67 [This is because the vorticity advection term arising from the left-hand-side of Eq.…”
Section: Most Stable Blob Sizementioning
confidence: 99%
“…If g jj is high enough, theory predicts that the path of least resistance is perpendicular to the field lines and the circuit closes in the divertor region. 43,48,121 In diverted tokamaks, where the main plasma is bounded by a separatrix, the X-point can disconnect both the linear perturbations, 111,254 and the current flow for the nonlinear blobs, 39,40,48,73 from the divertor region. The disconnection occurs because a blob (flux tube) that has a circular cross-section at the midplane is stretched into a thin ellipse (even approaching an ion gyroradius in thickness) near the X-point by the magnetic field line mapping.…”
Section: Blob Equivalent Circuitmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, despite their large use in analyzing the blob dynamics (see, e.g., Refs. [4][5][6][7][8][9][10][11][12]), a detailed validation project of seeded blob simulations has not been carried out yet. Herein, two-dimensional and three-dimensional simulations of seeded blobs, based on five different models implemented in four turbulence codes (BOUT++ 13 , GBS 14 , HESEL 15,16 , and TOKAM3X 17 ), are validated against experimental blob measurements.…”
Section: Introductionmentioning
confidence: 99%